my question is please give my answers
Attachments:
![](https://hi-static.z-dn.net/files/dd5/ce8d1db2166d850e8d4136cd61c4a126.jpg)
Answers
Answered by
2
p(x) = 3x²+5x-2
p(a)= 3(a)²+5(b)-2
= 3×a+5×b-2
= 3a+5b-2
=8ab-2
=6ab
p(a)= 3(a)²+5(b)-2
= 3×a+5×b-2
= 3a+5b-2
=8ab-2
=6ab
Answered by
1
3x²+5x-2=0
3x²+6x-x-2=0
3x(x+2)-1(x+2)=0
(3x-1)(x+2)=0
a=1/3 b=-2
2a=2/3
2b=-4
x²-(2a+2b)x+(2a)(2b)
=x²+10/3x-8/3
=3x²+10x-8
∴The required polynomial is 3x²+10x-8
3x²+6x-x-2=0
3x(x+2)-1(x+2)=0
(3x-1)(x+2)=0
a=1/3 b=-2
2a=2/3
2b=-4
x²-(2a+2b)x+(2a)(2b)
=x²+10/3x-8/3
=3x²+10x-8
∴The required polynomial is 3x²+10x-8
laksssss:
Pls mark as brainliest
Similar questions